Avaliação de Hb A2 e Hb F em doadores de sangue de região malarígena da Amazônia Oriental brasileira por HPLC - Souza, Wanessa C. [UNESP]; Torres, Felipe R. [UNESP]; Salvador, Ana R. [UNESP]; Távora, Juvanete A.; Machado, Ricardo L. D.; Bonini-Domingos, Cláudia R. [UNESP] (Associação Brasileira de Hematologia e Hemoterapia e daSociedade Brasileira de Transplante de Medula Óssea, 2003)
In malaria endemic regions of Africa, resistance to infection by Plasmodium has been observed in under 6-month-old children, when there are higher fetal hemoglobin (Hb F) levels. Research performed in the São José do Rio Preto region, central-east Brazil, reported increased levels of Hb F in blood donors. The purpose of this work was to evaluate the A2 hemoglobin (Hb A2) and Hb F concentrations in blood donors deriving from the Brazilian malaria endemic region. Forty-five blood donor samples from Macapá, from patients with varying genders, ages and ethnic origins, were collected by venous puncture after informed consent was obtained. The samples were analyzed by High Performance Liquid Chromatography (HPLC) - System Variant (Bio-Rad). The HPLC demonstrated sensitivity and rapidity in the identification and measurement of the hemoglobins and gave precise results. Moreover, it provided measurement of hemoglobin variants, even when they were present in small amounts, providing a diagnosis of hemoglobinopathies. Hb F levels above the normal were observed in 33.3% of the analyzed samples. The presence of increased Hb F can suggest resistance to infection by Plasmodium falciparum, as there have been reports that infected red blood cells interfere in the development of the parasite.
Evaluation of Hb A2 and Hb F by HPLC in blood donors from the malaria endemic region of Eastern Amazon of Brazil
Keywords: Hemoglobin S; Malaria; Genetic polymorphism; Blood donors; Amazon region